Southern Ocean control on atmospheric CO2 changes across late Pliocene Marine Isotope Stage M2 - S. Hou; L. Toebrock; M. van der Linden; F. Rothstegge; M. Ziegler; L. J. Lourens; P. K. Bijl (Climate of the Past)
During the Pliocene, atmospheric CO2 concentrations (pCO2) were probably sometimes similar to today's, and global average temperature was ∼3 °C higher than preindustrial. However, the relationships and phasing between variability in climate and pCO2 on orbital timescales are not well understood. Specifically, questions remain about the nature of a lag of pCO2 relative to benthic foraminiferal δ18O in late Pliocene Marine Isotope Stage (MIS) M2 (3300 ka), which was longer than during the Pleistocene. Here, we present a multiproxy paleoceanographic reconstruction of the late Pliocene subtropical–subantarctic zone. New dinoflagellate cyst assemblage data are combined with previously published sea surface temperature reconstructions to reveal past surface conditions, including latitudinal migrations of the subtropical front (STF) over the late Pliocene at Ocean Drilling Program (ODP) Site 1168, offshore of western Tasmania. We observe strong oceanographic variability at the STF over glacial–interglacial timescales, especially the interval (3320–3260 ka) across MIS M2. By providing tight and independent age constraints from benthic foraminiferal δ18O, we find that, much more than benthic δ18O or local SST, latitudinal migrations of the STF are tightly coupled to global pCO2 variations across the M2. Specifically, a northerly position of the STF during the MIS M2 deglaciation coincides with generally low pCO2. We postulate that the Southern Ocean CO2 outgassing varied strongly with migrations of the STF and that this in part accounted for the variability in pCO2 across MIS M2.